Mechanics, analysis and geometry : 200 years after Lagrange - Francaviglia, M. (North-Holland delta series., 1991)
Providing a logically balanced and authoritative account of the different branches and problems of mathematical physics that Lagrange studied and developed, this volume presents up-to-date developments in differential goemetry, dynamical systems, the calculus of variations, and celestial and analytical mechanics.